Trauma without event: Structural violence and gendered survival in Leila Mottley’s Nightcrawling - Dulfqar Mhaibes Abdulrazzaq (Universitas Sanata Dharma, 2026)
This article examines Leila Mottley’s Nightcrawling (2022) through the lens of Postclassical Trauma Theory, arguing that the novel redefines trauma as a structural and cultural condition rather than a singular psychological wound. A notable critical gap remains in the limited application of Postclassical Trauma Theory to Nightcrawling, particularly in relation to the interconnected experiences of urban displacement, precarity, policing, and gendered vulnerability. This study adopts a qualitative interpretive approach grounded in close textual analysis and guided by Postclassical Trauma Theory, with attention to concepts such as cultural trauma, structural violence, collective memory, and gendered embodiment. Moving beyond classical models of individual suffering, the study explores how trauma in Nightcrawling emerges through collective deprivation, systemic neglect, and the normalization of violence within Oakland’s marginalized communities. The analysis demonstrates that Mottley portrays trauma as an environmental and intergenerational phenomenon, embedded in social institutions such as housing, policing, and incarceration. Drawing on the works of Michelle Balaev, Stef Craps, and Saidiya Hartman, the article contends that the novel articulates a distinctly postclassical vision of trauma—one shaped by communal grief, precarity, and gendered vulnerability. Kiara’s experiences of poverty, sexual exploitation, and familial absence reveal how trauma operates across social and bodily terrains, linking personal endurance to broader cultural survival. Ultimately, the study argues that Nightcrawling transforms trauma from an individual memory into a collective archive of resilience, asserting the need to reimagine trauma narratives within the intersecting frameworks of race, gender, and systemic inequality